Modeling, simulation and feasibility study of the Parabolic Dish System under Malaysia environment - Affandi, Rosnani (UTeM, 2016)
The primilarily aim of this research is to carry out the fundamental investigation of the performance and feasibility of solar CSP, focusing on Parabolic Dish (PD) type in Malaysia environment. Three main components of the PD system that is under consideration, consists of the concentrator, the receiver, and the Stirling engine. By using a simulation approach and Matlab Simulink as the simulation tool; a background of the PD system is provided, along with a detailed description of the components model. Meanwhile, the performance for the three main components in PD system, is examined under three solar irradiance conditions that are low, medium and high. Besides that, the geometric design for the concentrator and receiver as well as the site location for this study is given through emphasis. Therefore, concentrator in PD system use reflective material with high efficiency to increase the PD concentrator efficiency, choose high value for the intercept factor to reduce loss for the solar intercept by the receiver and select a site with excellent solar irradiation in order to achieve high efficiency and as a result can produce high output power. Thus, by considering the highest Direct Solar Irradiance (DNI) and based on regions, five sites or locations has been chosen for this study. The site or locations with highest DNI in Malaysia are George Town at the Northern part of Peninsular Malaysia. Meanwhile, other locations are Subang in central of Peninsular Malaysia, Kuantan on the east coast of peninsular Malaysia, Senai in the Southern part of peninsular Malaysia and Kuching located in East Malaysia. To accomplish the research objectives, the performance of the PD system under Malaysia environment and the output from each of the main components were analyzed. In addition, the feasibility study in terms of technical and economic are thoroughly investigated. This includes defining the characteristics and constraints, as well as the overall system performance in monetary term. The PD system are considered feasible if the PD system reaches 54,750 kW of yearly output power, capacity factor reach the value around 25 – 28% and the Levelized Cost of Electricity (LCOE) lies between RM1.72/kWh and RM 0.7522/kWh. However, the result of this research has shown that the system is technically feasible but not economically feasible. T he yearly output power, the annual energy and the capacity factor shows that the PD system in Malaysia are not capable of meeting the demand reliably. Thus, the new developed model for the 25kW PD system and the finding of this research can provide useful information for Malaysia regulators on the potential of CSP development in Malaysia or in other equator region countries.